Assessing Use of a Standardized Dental Diagnostic Terminology in an Electronic Health Record. Issue 1 (1st January 2013) - Tokede, Oluwabunmi; White, Joel; Stark, Paul C.; Vaderhobli, Ram; Walji, Muhammad F.; Ramoni, Rachel; Schoonheim‐Klein, Meta; Kimmes, Nicole; Tavares, Anamaria; Kalenderian, Elsbeth
Abstract : Although standardized terminologies such as the International Classification of Diseases have been in use in medicine for over a century, efforts in the dental profession to standardize dental diagnostic terms have not achieved widespread acceptance. To address this gap, a standardized dental diagnostic terminology, the EZCodes, was developed in 2009. Fifteen dental education instutions in the United States and Europe have implemented the EZCodes dental diagnostic terminology. This article reports on the utilization and valid entry of the EZCodes at three of the dental schools that have adopted this standardized dental diagnostic terminology. Electronic data on the use of procedure codes with diagnostic terms from the three schools over a period from July 2010 to June 2011 were aggregated. The diagnostic term and procedure code pairs were adjudicated by three calibrated dentists. Analyses were conducted to gain insight into the utilization and valid entry of the EZCodes diagnostic terminology in the one‐year period. Error proportions in the entry of diagnostic term (and by diagnostic category) were also computed. In the twelve‐month period, 29, 965 diagnostic terms and 249, 411 procedure codes were entered at the three institutions resulting in a utilization proportion of 12 percent. Caries and periodontics were the most frequently used categories. More than 1, 000 of the available 1, 321 diagnostic terms were never used. Overall, 60.5 percent of the EZCodes entries were found to be valid. The results demonstrate low utilization of EZCodes in an electronic health record and raise the need for specific training of dental providers on the importance of using dental diagnostic terminology and specifcally how to use the terms in the electronic record. These findings will serve to increase the use/correct use of the EZCodes dental diagnostic terminology and ultimately create a reliable platform for undertaking clinical, outcomes, and quality improvement‐related research.